Altered proTGFα/cleaved TGFα ratios offer new therapeutic strategies in renal carcinoma - Sara García-Alonso; Inés Romero-Pérez; Lucía Gandullo-Sánchez; Luis Chinchilla; Alberto Ocaña; Juan Carlos Montero; Atanasio Pandiella (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Background Treatment of renal cancer has significantly improved with the arrival to the clinic of kinase inhibitors and immunotherapies. However, the disease is still incurable in advanced stages. The fact that several approved inhibitors for kidney cancer target receptor tyrosine kinases (RTKs) suggests that these proteins play a critical role in the pathophysiology of the disease. Based on these precedents, we decided to explore whether RTKs other than those targeted by approved drugs, contribute to the development of kidney cancer. Methods The activation status of 49 RTKs in 44 paired samples of normal and tumor kidney tissue was explored using antibody arrays, with validation by western blotting. Genetic and pharmacologic approaches were followed to study the biological implications of targeting the epidermal growth factor receptor (EGFR) and its ligand Transforming Growth Factor-α (TGFα). Results Activation of the EGFR was found in a substantial number of tumors. Moreover, kidney tumors expressed elevated levels of TGFα. Down-regulation of EGFR or TGFα using RNAi or their pharmacological targeting with blocking antibodies resulted in inhibition of the proliferation of in vitro cellular models of renal cancer. Importantly, differences in the molecular forms of TGFα expressed by tumors and normal tissues were found. In fact, tumor TGFα was membrane anchored, while that expressed by normal kidney tissue was proteolytically processed. Conclusions The EGFR-TGFα axis plays a relevant role in the pathophysiology of kidney cancer. This study unveils a distinctive feature in renal cell carcinomas, which is the presence of membrane-anchored TGFα. That characteristic could be exploited therapeutically to act on tumors expressing transmembrane TGFα, for example, with antibody drug conjugates that could recognize the extracellular region of that protein.